2014
DOI: 10.1097/pcc.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of Anakinra, an Interleukin-1 Receptor Antagonist, in the Management of Secondary Hemophagocytic Lymphohistiocytosis/Sepsis/Multiple Organ Dysfunction/Macrophage Activating Syndrome in Critically Ill Children*

Abstract: Anakinra could represent a promising therapeutic approach in these life-threatening disorders that are likely underdiagnosed and often difficult to treat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 31 publications
2
136
0
1
Order By: Relevance
“…In SJIA-related MAS, the hallmark of therapy is pulse steroids and cyclosporine A with refractory disease being treated with IVIg, rituximab (in EBV-associated MAS), alemtuzumab, daclizumabor anti-cytokine therapies including anti-IL-1 and anti-IL-6 (44, 45). For patients with IAHS, specific therapies directed at controlling infection may be sufficient for disease control (44).…”
Section: Therapeuticsmentioning
confidence: 99%
“…In SJIA-related MAS, the hallmark of therapy is pulse steroids and cyclosporine A with refractory disease being treated with IVIg, rituximab (in EBV-associated MAS), alemtuzumab, daclizumabor anti-cytokine therapies including anti-IL-1 and anti-IL-6 (44, 45). For patients with IAHS, specific therapies directed at controlling infection may be sufficient for disease control (44).…”
Section: Therapeuticsmentioning
confidence: 99%
“…Although his strategy is focused on only EBV-associated HLH, we believe that it can be generalised to HLH triggered by other agents. Rajasekaran et al 22 reported successful treatment of eight paediatric intensive care unit patients with presumed secondary HLH with IL-1R antagonist (anakinra). Thus treatment of HLH could be directed to those particular cytokines that are causing organ damage in addition to, or in place of non-specific immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, results of the protocol were published with 5-year survival rates reaching 54%. 15 More recent studies 16,17 indicate that there may be a benefit in diagnosing FHL versus acquired HLH irrespective of the need for hematopoietic stem cell transplantation in the former. A Turkish study with a small sample size found that therapeutic plasma exchange and intravenous immunoglobulin with methylprednisone was found to be effective in patients diagnosed with acquired HLH and was less toxic than the chemotherapeutic regimen outlined by the Histiocyte Society.…”
Section: Managementmentioning
confidence: 98%
“…The interleukin-1 inhibitor, anakinra, was associated with a decrease in inflammatory markers in a small cohort of pediatric intensive care patients with presumed secondary HLH, but results were confounded by additional therapies. 17 More outcomes studies are needed to elucidate which treatment protocols have the best survival and safety profiles.…”
Section: Managementmentioning
confidence: 99%